Programa brasileiro de acreditação hospitalar: sua influência no credenciamento de hospitais em operadoras de plano de saúde - Martelotte, Marcela Cohen (2003)
This dissertation presents the result of a study accomplished on the degree of use of the certificate of hospital Accreditation as one of the criteria for the accreditation of hospitals by the health insurance companies. Should be emphasized that the Accreditation Certificate represents the main final product of Hospital Accreditation Brazilian Program, being the first emitted when the hospital assists to the quality patterns specified by the Program. In that way, the study focus was, in general terms, Hospital Accreditation Brazilian Program and, more strictly, the Accreditation Certificate and it use. To reach the objectives proposed by the study, interviews were accomplished with the professionals responsible for the accreditation of the hospitals in the main health insurance companies of Brazil. In the total, five companies were consulted among the ten larger health insurance companies of Brazil, considering the number of beneficiaries. To complement the research, additional information were collected in the National Agency of Supplemental Health. It was verified, through the research, that the health insurance companies don't use the Accreditation Certificate given by the Hospital Accreditation Brazilian Program to accredit hospitals.